indonesia - Yusmarini Yusmarini; Yossie Kharisma Dewi; Usman Pato; Shanti Fiftriani; Emma Riftyan; Edo Saputra (Unri Conference Series: Community Engagement, 2022)
Orange and pineapple juice drinks are one of the products that have been made by UKM Desa Pulau Jambu. The processing of the fruit juice drink is still done manually for the whole process. The purpose of this service activity is to provide innovation in the processing of orange and pineapple juice drinks. The method implemented in this community service activity is to provide guidance and training from the production aspect. The training provided is the processing of orange and pineapple juice using the development of processing technology in the form of a semi-automatic orange and pineapple juice mixer machine. The automatic mixer is proven to be able to facilitate the production process of orange and pineapple juice drinks compared to manual mixing.